Construction of Weifang Handicraft Industry Brand System in the Industry 4.0 Era - Zhang Zhichao (SHS Web of Conferences)
As a distinct component of the local economy, Weifang’s traditional handicraft sector not only contains countless intangible cultural heritages, but it also serves as a significant driving force in encouraging local economic progress. However, the establishment of a brand system is a vital step toward upgrading, cultural inheritance, and commercial expansion in the handicraft business. However, most handcraft brands in Weifang have poor brand construction, slow development, and even shrinking. This essay, written in the context of the sector 4.0 era, examines the current state of the branding process in the Weifang handicraft sector. It examines the path of brand systematization construction in the Weifang handicraft industry from multiple perspectives, including brand awareness, brand positioning, brand derivation, and brand communication, with the goal of encouraging creative transformation and innovative development that meets contemporary needs.